Development Of The Potential Of The Angke Kapuk Mangrove Forest Natural For Ecotourism In Kamal Muara Village, Penjaringan Sub-District, North Jakarta - Juliati Prihatini; Achmad Nur Sutikno; Johan Iskandar (AIBPM Publisher, 2023)
Mangrove forest ecosystem has various ecological, socio-economic and cultural functions for society, such as for nature tourism or ecotourism activities. The purpose of this article is to discuss the potential for the development of the Angke Kapuk Mangrove Forest Nature Park (TWA), North Jakarta for ecoturism activities. The research method used in this study was qualitative method. The results of the study showed that there are various strengths that are potential for the Angke Mangrove Forest to be developed for ecotourism, such as the strategic location of tourist attractions, the presence of natural tourism objects, and the existence of interesting a variety of flora and fauna species of mangroves for visitors. However, the Angke Kapuk Mangrove Forest still has some weaknesses. Therefore, for the development of these natural tourism or ecotourism areas in the future, it is necessary to pay attention to the principles of ecotourism, such as tourism activities must minimize negative impacts on the environment, the need to increase the active participation of local residents.